Use of herb, Bala(Sida cordifolia Linn.) as growth promoter in the supplementary feed of Cirrhinus mrigala(Ham.) - Kour, Dalweer; Sharma, L L; Sharma, B K (Indian Journal of Fisheries, 2011)
Use of herb, Bala(Sida cordifolia Linn.) as growth promoter in the supplementary feed of Cirrhinus mrigala(Ham.)